Possible applications of nano-spun fabrics and materials. (2017) - Grothe, Timo; Grimmelsmann, Nils; Homburg, Sarah V.; Ehrmann, Andrea
Abstract: Nano-spun fabrics can be used in diverse applications. One of the most promising sectors for these novel materials is medical healthcare. As an example, bandages coated with Aloe vera nano-fiber mats can be used in medicine as wound dressing for first degree burns and other wounds. The Aloe vera fiber mats form a hydrogel when getting wet and are reported to result in faster wound healing, increased degree of collagen cross linking, antiseptic properties etc. Similarly, cross-linked alginate can be used as a wound dressing, with the opposite effect of Aloe Vera. Nano-spun alginate fiber mats are dry but can absorb a large quantity of water or wound fluid and thus support drying of bleeding wounds. Our presentation gives an overview of recent developments in electrospinning nano-fiber mats from biopolymers such as Aloe vera and alginate, possible applications and the latest research results in needleless electrospinning biopolymers from aqueous solutions.